The Emerald International Handbook of Technology-Facilitated Violence and Abuse 2021
DOI: 10.1108/978-1-83982-848-520211005
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Technology-Facilitated Violence and Abuse among Young Adults in Sub-Saharan Africa

Abstract: Incidents of violence perpetrated through digital technology platforms or facilitated by these means have been reported, often in high-income countries. Very little scholarly attention has been given to the nature of Technology-Facilitated violence and abuse (TFVA) across sub-Saharan Africa (SSA) despite an explosion in the use of various technologies. We conducted a literature review to identify and harmonize available data relating to the types of TFVA taking place in SSA. This was followed by an online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Besides, nearly half of all pregnancies among young women in developing countries, including sub-Saharan Africa, are unintended and result in a significantly high number of unintended births and unsafe abortions (Darroch et al, 2016). More than 80% of young men and women in sub-Saharan African countries also reported being victims of technology-facilitated sexual, gender-based and other forms of violence (Makinde et al, 2021). Given the scale of sexual health challenges in African countries, there is an increasing need to reduce infection rates, unplanned pregnancies, and other related abuses among adolescents and young adults in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, nearly half of all pregnancies among young women in developing countries, including sub-Saharan Africa, are unintended and result in a significantly high number of unintended births and unsafe abortions (Darroch et al, 2016). More than 80% of young men and women in sub-Saharan African countries also reported being victims of technology-facilitated sexual, gender-based and other forms of violence (Makinde et al, 2021). Given the scale of sexual health challenges in African countries, there is an increasing need to reduce infection rates, unplanned pregnancies, and other related abuses among adolescents and young adults in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Image-Based Sexual Abuse. The non-consensual taking, sharing, or threats to share personal, intimate images or videos were reported in most of the included studies, highlighting how IBSA is used to blackmail, humiliate, or perpetrate emotional abuse (França & Quevedo, 2020;Hassan et al, 2020;Jatmiko et al, 2020;Makinde et al, 2021;Sarkar & Rajan, 2021;Zagloul et al, 2022). A study conducted by Zagloul et al (2022) of Egyptian women (n = 563) found that more than half (51.9%) of study participants experienced non-consensual pornography.…”
Section: Types and Patterns Of Tfsva In Lmicsmentioning
confidence: 99%
“…Monitoring Through Digital Technologies. Some studies found that women were being monitored or their activities tracked through digital tools and technologies (Hassan et al, 2020;Makinde et al, 2021). An online survey of Egyptian women found that 1 in 10 (11.5%, total n = 148) reported that their online and offline activities were monitored or tracked, 6% said that their private data and/or photos were accessed and spread without permission and 5% reported that their movements were tracked (Hassan et al, 2020).…”
Section: Types and Patterns Of Tfsva In Lmicsmentioning
confidence: 99%
See 2 more Smart Citations